1996
DOI: 10.1128/iai.64.7.2500-2505.1996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking and race on immunoglobulin G subclass concentrations in early-onset periodontitis patients

Abstract: Recent data indicate that smoking is an important risk factor for the development of periodontitis. Smoking is also known to reduce serum immunoglobulin G (IgG) levels. Interestingly, patients with the localized form of early-onset periodontitis (LJP) have elevated levels of serum IgG2, and those who smoke are not clinically different from nonsmoking LJP subjects. In contrast, patients with the generalized form of early-onset periodontitis (G-EOP) who smoke have more extensive destruction than their nonsmoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
3
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 35 publications
3
74
3
4
Order By: Relevance
“…It should also be emphasized that in the present study, responsiveness to infecting bacteria was also analysed by means of infection ratios that reflect a combined measure of both colonization and ab response and are biologically more relevant than the mere study of ab titres. Obviously, we cannot rule out that part of the discrepancy between our findings and those of other studies in the literature can be ascribed to the limited size of the examined sample or be attributed to variance because of specific subject sample characteristics such as race/ethnicity or smoking habits, both of which have been shown to affect ab levels and the proportion of specific serum IgG subclasses (Quinn et al 1996, 1998, Albandar et al 2002. However, in all likelihood, the discrepancy is mainly because of the fact that, according to the current guidelines, the diagnosis of either chronic or aggressive periodontitis can be assigned to individuals of any age, rendering inferences based on patients with early-onset periodontitis not applicable.…”
Section: Discussioncontrasting
confidence: 99%
“…It should also be emphasized that in the present study, responsiveness to infecting bacteria was also analysed by means of infection ratios that reflect a combined measure of both colonization and ab response and are biologically more relevant than the mere study of ab titres. Obviously, we cannot rule out that part of the discrepancy between our findings and those of other studies in the literature can be ascribed to the limited size of the examined sample or be attributed to variance because of specific subject sample characteristics such as race/ethnicity or smoking habits, both of which have been shown to affect ab levels and the proportion of specific serum IgG subclasses (Quinn et al 1996, 1998, Albandar et al 2002. However, in all likelihood, the discrepancy is mainly because of the fact that, according to the current guidelines, the diagnosis of either chronic or aggressive periodontitis can be assigned to individuals of any age, rendering inferences based on patients with early-onset periodontitis not applicable.…”
Section: Discussioncontrasting
confidence: 99%
“…Alterations in gingival crevicular fluid [68][69][70] and peripheral blood mononuclear cell 71 levels of various cytokines in smokers, tipping the balance in favor of tissue breakdown, have been noted. Smoking decreases salivary IgA 72 and serum IgG, 73 and specifically reduces IgG2 to A. actinomycetemcomitans. 74 The ability of tobacco products to decrease the proliferative capacity of T and B lymphocytes might contribute to this diminished production of protective antibodies.…”
Section: Smoking and The Host Responsementioning
confidence: 97%
“…It has been reported that smokers harbor a higher prevalence of potential periodontal pathogens. [11][12][13] In addition, smoking impairs various aspects of the innate and immune host responses, including neutrophil functions, 14,15 antibody production, 16,17 fibroblast activities, 18,19 and inflammatory mediator production. [20][21][22] It has been well documented that smokers exhibit greater bone loss and attachment loss, 23 as well as a higher prevalence of deep periodontal pockets than non-smokers.…”
Section: Introductionmentioning
confidence: 99%